Evaluasi Pembelajaran Siswa Kelas IV di SDN Cengklong III - Ina Magdalena; Roudhotus Sabila; Tri Widyastuti (Jurnal Halaqah, 2021)
This article was created to determine the learning evaluation activities that have been carried out at SDN Cengklong III, Tangerang Regency. In this study the authors used a qualitative research approach through interviews and data analysis. The results of this study indicate that the implementation of learning evaluation at SDN Cengklong III Tangerang Regency has been going well, but there are differences, namely verbally can answer, but when given in writing, they lack confidence in answering them.